How do Candida glabrata´s biofilms respond to antifungal drugs? - Rodrigues, Célia Fortuna (2015)
Candida species are responsible for recurrent human infections, mostly in immunocompromised patients, due to their high vulnerability. Candida glabrata has been shown to have a major role in these infections being the second most prevalent species involved in human fungemia. Objective: To understand the effect of three different antifungal agents Fluconazole (Flu), Amphotericin B (AmB) and Caspofungin (Csf) - in C. glabratas biofilm formation, specially their role on matrix composition.